Method for preparing boron nitride self-supporting film through electrostatic spinning and film

The preparation of boron nitride self-supporting films through electrospinning technology solves the problem of insufficient strength of traditional films, and achieves high strength, low thermal resistance and excellent thermal conductivity, insulation and wave transmission performance, which is suitable for a variety of high-performance applications.

CN119753947AActive Publication Date: 2025-04-04CHINA NORTH ENGINE INST TIANJIN
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510048390.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

Traditional boron nitride self-supporting films have low strength and lack strong fiber coordination, making it difficult to meet the needs of high thermal conductivity, insulation and wave transmissive properties.

Method used

Through electrospinning technology, boron nitride nanotubes and boron nitride nanosheets are dispersed in an organic solution, ultrasonic peeling and oxygen plasma treatment are performed to form a hydroxylated boron nitride mixed powder, and soaked in a silane coupling agent for amidation. Then it is mixed with aramid nanofibers, electrospinning is performed, and finally high-temperature hot pressing is performed to obtain a boron nitride self-supporting film.

Benefits of technology

It has achieved high strength, low thermal resistance, excellent thermal conductivity, insulation and wave transmission performance of boron nitride self-supporting film, and is suitable for 5G base stations, mobile phone antennas and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753947A_ABST
    Figure CN119753947A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a boron nitride self-supporting film through electrostatic spinning and the film. The method comprises the following steps: S1, preparing mixed powder of boron nitride nanotubes and boron nitride nanosheets; s2, hydroxylated boron nitride mixed powder is obtained; s3, soaking the obtained hydroxylated boron nitride mixed powder in a silane coupling agent, and stirring to obtain polydopamine modified amidated boron nitride, wherein the silane coupling agent is 3-urea propyl trimethoxy silane; s4, carrying out ultrasonic treatment to obtain a boron nitride aramid nanofiber suspension, wherein the mass percentage of aramid nanofibers in the aramid nanofiber ethanol solution is 3-8wt%; and S5, carrying out electrostatic spinning on the boron nitride aramid nanofiber suspension obtained in the step S4 to obtain a film, and carrying out high-temperature hot-pressing treatment on the film to obtain the boron nitride self-supporting film. The boron nitride self-supporting film prepared by the invention has the characteristics of high thermal conductivity, ultralight weight, high toughness, high wave permeability, excellent dielectric property and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano ceramic film materials, and in particular relates to a method for preparing a boron nitride self-supporting film by electrostatic spinning and the film. Background Art

[0002] Electrospinning is a special fiber manufacturing process in which a polymer solution or melt is jet-spun in a strong electric field. Under the action of the electric field, the droplet at the needle tip changes from a sphere to a cone (i.e., a "Taylor cone"), and fiber filaments extend from the tip of the cone. This method can produce polymer filaments with nanometer diameters.

[0003] Boron nitride and graphite have very similar structures. Whether it is layered or tubular, boron nitride has excellent thermal conductivity and mechanical properties like graphene or carbon nanotubes. However, compared with graphene or carbon nanotubes, boron nitride has better thermal stability, insulation and wave transmission performance. At present, the thermal conductivity of graphite self-supporting films is as high as 1500W / mK, which has great application value in the field of thermal conductivity. However, graphite thermal conductive films are extremely conductive and have a large shielding effect on electromagnetic waves, which makes it difficult for graphite self-supporting films to be widely used in the fields of insulation, thermal conductivity and wave transmission such as 5G base stations and mobile phone antennas. Boron nitride self-supporting films have both good thermal conductivity and excellent insulation and wave transmission properties. Traditional boron nitride self-supporting films are based on boron nitride nanosheets and are prepared by filtration. The boron nitride self-supporting film prepared by this method has low strength due to the lack of strong fiber synergy. Summary of the invention

[0004] In view of this, the present invention aims to provide a method for preparing a boron nitride self-supporting film by electrospinning and the film, so as to solve at least one technical problem in the background technology.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows: The method for preparing a boron nitride self-supporting film by electrospinning and the film include the following steps: S1: dispersing boron nitride nanotubes and boron nitride nanosheets in an organic solution to prepare a boron nitride slurry, subjecting the boron nitride slurry to ultrasonic exfoliation and centrifugation to obtain a precipitate, and freeze-drying the precipitate to obtain a mixed powder of the boron nitride nanotubes and boron nitride nanosheets; S2: treating the mixed powder of boron nitride nanotubes and boron nitride nanosheets obtained in step S1 with oxygen plasma to obtain hydroxylated boron nitride mixed powder; S3: soaking the hydroxylated boron nitride mixed powder obtained in step S2 in a silane coupling agent, stirring to obtain hydroxylated boron nitride, and soaking the hydroxylated boron nitride in polydopamine, stirring to obtain polydopamine-modified amidated boron nitride; S4: the amidated boron nitride modified with polydopamine obtained in step S3 is mixed with the aramid nanofiber ethanol solution, and subjected to ultrasound to obtain a boron nitride aramid nanofiber suspension; S5: electrospinning the boron nitride aramid nanofiber suspension obtained in step S4 to obtain a film, and subjecting the film to high-temperature hot pressing to obtain a boron nitride self-supporting film.

[0006] Furthermore, in step S1, the length of the boron nitride nanotube is 50-150 μm, and preferably, the length of the boron nitride nanotube is 150 μm.

[0007] And / or, in step S1, the diameter of the boron nitride nanotube is 50-150 nm, preferably, the diameter of the boron nitride nanotube is 50 nm.

[0008] In step S1, the wall thickness of the boron nitride nanotube is 10-30 nm, and preferably, the wall thickness of the boron nitride nanotube is 10 nm.

[0009] And / or, the median diameter of the boron nitride nanotubes in step S1 is 50-150 nm. Preferably, the median diameter of the boron nitride nanotubes in step S1 is 50 nm.

[0010] And / or, in step S1, the lateral length of the boron nitride nanosheet is 50-200 nm, preferably, the lateral length is 200 nm.

[0011] The thickness of the boron nitride nanosheets is 30-50 nm, preferably 30 nm.

[0012] Furthermore, the solid content of the boron nitride slurry in step S1 is 30% to 70%. Preferably, the solid content of the boron nitride slurry in step S1 is 60%.

[0013] And / or, the organic solution in step S1 includes one or more of ethanol, dimethyl sulfoxide, dichloromethane, tetrahydrofuran, toluene, and dimethylformamide. Preferably, the organic solution in step S1 is one of tetrahydrofuran and dimethylformamide.

[0014] And / or, the time for ultrasonic stripping of the boron nitride slurry in step S1 is 24 to 72 hours; And / or, the boron nitride slurry after ultrasound in step S1 is centrifuged, and the centrifugation includes low-speed centrifugation and high-speed centrifugation, wherein the rotation speed of the low-speed centrifugation is 1000-3000 r / min, and the centrifugation time of the low-speed centrifugation is 10-25 min; preferably, the rotation speed of the low-speed centrifugation is 3000 r / min, the centrifugation time of the low-speed centrifugation is 15 min, the rotation speed of the high-speed centrifugation is 8000-20000 r / min, and the centrifugation time of the high-speed centrifugation is 15-45 min, preferably, the rotation speed of the high-speed centrifugation is 11000 r / min, and the time of the high-speed centrifugation is 30 min.

[0015] And / or, the freeze-drying temperature in step S1 is: -78~-82°C, preferably, the freeze-drying temperature is 80°C, and the time is 24~48h.

[0016] And / or, the ultrasonic exfoliation time of the boron nitride slurry in step S1 is 48 hours.

[0017] Furthermore, in step S2, the oxygen plasma treatment time is 20 to 60 minutes, and preferably, the oxygen plasma treatment time is 30 minutes.

[0018] Further, in step S3, the silane coupling agent is 3-ureapropyltrimethoxysilane; And / or, in step S3, the hydroxylated boron nitride mixed powder is immersed in the silane coupling agent for 1 to 5 hours, preferably, for 3 hours.

[0019] And / or, after the hydroxylated boron nitride mixed powder is immersed in the silane coupling agent in step S3, it is stirred at a speed of 100 to 500 r / min, preferably, the speed of stirring is 300 r / min, the temperature of stirring is 40 to 80°C, preferably, the temperature is 60°C, and the stirring time is 30 to 60 min.

[0020] And / or, the concentration of polydopamine in step S3 is 1-4%, preferably, the concentration of polydopamine in step S3 is 2%.

[0021] The hydroxylated boron nitride is amidated and immersed in polydopamine at room temperature for 1 to 5 hours, preferably for 3 hours.

[0022] Furthermore, the preparation method of the aramid nanofiber ethanol solution in step S4 comprises the following steps: dissolving and immersing the aramid nanofiber in ethanol to obtain the aramid nanofiber ethanol solution, the immersion temperature of the aramid nanofiber in ethanol is 50-90°C, preferably, the immersion temperature is 70°C, and the immersion time is 1.8-2.2h.

[0023] The mass percentage of the aramid nanofiber ethanol solution in step S4 is 3-8wt%, preferably, the mass percentage is 5wt%.

[0024] The soaking time is 1.8-2.2 hours, preferably, the soaking time is 2 hours.

[0025] And / or, in step S4, the ultrasonic time after the amidated boron nitride modified with polydopamine is mixed with the aramid nanofiber ethanol solution is 1 to 2 hours; The solid content of the boron nitride aramid nanofiber suspension in step S4 is 30-70%, preferably, the solid content is 50%.

[0026] Furthermore, in step S5, the prepared boron nitride aramid nanofiber suspension is divided into 20 portions and electrospun in a staggered manner of 10 vertically and 10 horizontally.

[0027] Furthermore, in step S5, the surface of the receiving disc in the electrospinning is covered with polytetrafluoroethylene, and the rotation speed of the receiving disc is 1000-3000 r / min, preferably, the rotation speed of the receiving disc is 2500 r / min.

[0028] The spinning time of electrospinning is 0.5 to 3 hours, preferably, the spinning time is 3 hours.

[0029] And / or, the obtained film is subjected to heat pressing at a temperature of 100 to 300°C, with the temperature being 200°C.

[0030] Compared with the prior art, the method for preparing a boron nitride self-supporting film by electrospinning and the film described in the present invention have the following advantages: 1. This application uses nano-scale ultra-light, high-strength and tough boron nitride nanotubes as a matrix, uses boron nitride nanosheets to fill the gaps, and provides a low-cost, large-scale technical path for preparing ultra-high-strength boron nitride self-supporting films through vertical alternating spinning.

[0031] 2. This application avoids the major defect of low tensile strength of thermal conductive films prepared by traditional wet method of boron nitride nanosheets. By functionalizing and modifying the surface of boron nitride, strong interface bonding between boron nitride nanotubes is achieved, greatly reducing the thermal resistance between the interfaces of boron nitride. The strength of thermal conductive and wave-transmitting films is greatly improved by orderly cross-weaving of nanotubes. Aramid nanofibers are used to improve the viscosity and density of boron nitride.

[0032] 3. The electrospinning method adopted in the present invention can be used for large-scale and low-cost process preparation technology. At the same time, the boron nitride self-supporting film prepared by this method has the characteristics of high thermal conductivity, ultra-lightness, high strength and toughness, high wave transmittance, and excellent dielectric properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings: Figure 1 This is a diagram of a heat-conducting and wave-transmitting film prepared by electrospinning of boron nitride nanotubes and boron nitride nanosheets as described in Example 1 of the present invention; Figure 2 This is a schematic diagram of the internal structure of the heat-conducting and wave-transmitting composite film according to Example 1 of the present invention; Figure 3 These are microscopic SEM images of the heat-conducting and wave-transmitting composite film described in Example 1 of the present invention (the electron microscope magnification of a is 1000 times, the electron microscope magnification of b is 1800 times, the electron microscope magnification of c is 10000 times, and the electron microscope magnification of d is 18000 times). DETAILED DESCRIPTION

[0034] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0035] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.

[0036] Example 1

[0037] Boron nitride nanotubes with a diameter of 50nm, a length of 150μm, and a wall thickness of 10nm and boron nitride nanosheets with a transverse length of 200nm and a thickness of 30nm were selected as raw materials. Equal amounts of boron nitride nanotubes and boron nitride nanosheets were added to dimethylformamide to prepare a slurry with a solid content of 60%. The boron nitride slurry was then subjected to ultrasonic exfoliation for 48 hours. The ultrasonic slurry was then centrifuged at a low speed of 3000r / min for 15 minutes, and then subjected to high-speed centrifugation at a speed of 11000r / min for 30 minutes. The supernatant was then poured to obtain boron nitride nanotubes and boron nitride nanosheets precipitates. The slurry was then freeze-dried at -80°C for 48 hours. The freeze-dried mixed powder of boron nitride nanotubes and boron nitride nanosheets was treated with oxygen plasma for 30 minutes to obtain a hydroxylated boron nitride mixed powder. Then, the hydroxylated boron nitride mixed powder was immersed in 3-ureapropyltrimethoxysilane for 3 hours, and stirred at a speed of 300 r / min and a temperature of 60°C for 45 minutes to amidate the hydroxylated boron nitride. The hydroxylated boron nitride nanosheets s-OH of the boron nitride nanosheets interacted with the silanol obtained by hydrolysis of 3-ureapropyltrimethoxysilane to obtain nanosheets with amide groups at the end. 2 .

[0038] Add 2% polydopamine to the boron nitride slurry to modify the amidated boron nitride, soak at room temperature for 3 hours, and stir evenly. Then dissolve 5wt% aramid nanofibers in ethanol at 70℃ and soak for 2 hours. Add the soaked aramid nanofiber ethanol solution to the amidated boron nitride modified by polydopamine to prepare a boron nitride aramid nanofiber suspension of about 50%, and ultrasonicate for 2 hours. Divide the prepared boron nitride nanotube / boron nitride nanosheet / aramid nanofiber suspension into 20 portions and electrospin in a staggered manner of 10 vertical and 10 horizontal. Cover the surface of the receiving disc with polytetrafluoroethylene, adjust the speed to 2000r / min, and the spinning time is 3h. The obtained film is subjected to high temperature hot pressing at 200℃ to obtain a boron nitride self-supporting film. The obtained film has a strength of 30MPa, a thermal conductivity of 60W / mK, and a film density of 50g / m 2 , the porosity is 70%, the finished thermal conductive wave-transmitting film is Figure 1 As shown, the internal structure of the thermally conductive and wave-transmitting composite film is as follows Figure 2 As shown in Figure 2, the microstructure of the thermally conductive and wave-transmitting composite film is as follows: Figure 3 shown.

[0039] Example 2 Boron nitride nanotubes with a diameter of 50nm, a length of 50μm, and a wall thickness of 10nm and boron nitride nanosheets with a transverse length of 200nm and a thickness of 30nm were selected as raw materials. Equal amounts of boron nitride nanotubes and boron nitride nanosheets were added to tetrahydrofuran to prepare a slurry with a solid content of 60%. The boron nitride slurry was then subjected to ultrasonic exfoliation for 48 hours. The ultrasonic slurry was then centrifuged at a low speed of 3000r / min for 15 minutes, and then subjected to high-speed centrifugation at a speed of 11000r / min for 30 minutes. The supernatant was then poured to obtain boron nitride nanotubes and boron nitride nanosheets precipitates. The slurry was then freeze-dried at -80°C for 48 hours. The freeze-dried mixed powder of boron nitride nanotubes and boron nitride nanosheets was treated with oxygen plasma for 30 minutes to obtain a hydroxylated boron nitride mixed powder. Then, the hydroxylated boron nitride mixed powder was immersed in 3-ureapropyltrimethoxysilane for 3 hours, and stirred at a speed of 300 r / min and a temperature of 60°C for 45 minutes to amidate the hydroxylated boron nitride. The hydroxylated boron nitride nanosheets s-OH of the boron nitride nanosheets interacted with the silanol obtained by hydrolysis of 3-ureapropyltrimethoxysilane to obtain nanosheets with amide groups at the end. 2. Add 2% polydopamine to the boron nitride slurry to modify the amidated boron nitride, soak it at room temperature for 3 hours, and stir it evenly. Then dissolve 5wt% aramid nanofibers in ethanol at 70℃ and soak it for 2 hours. Add the soaked aramid nanofiber ethanol solution to the amidated boron nitride modified by polydopamine to prepare a boron nitride aramid nanofiber suspension of about 50%, and ultrasonicate it for 2 hours. Divide the prepared boron nitride nanotube / boron nitride nanosheet / aramid nanofiber suspension into 20 portions and electrospin in a staggered manner of 10 vertical and 10 horizontal. Cover the surface of the receiving disc with polytetrafluoroethylene, adjust the speed to 2000r / min, and the spinning time is 3h. The obtained film is subjected to high-temperature hot pressing at 200℃ to obtain a boron nitride self-supporting film. The obtained film has a strength of 15MPa, a thermal conductivity of 35W / mK, and a film density of 70g / m 2 , the porosity is 60%.

[0040] Example 3 Boron nitride nanotubes with a diameter of 50nm, a length of 50μm, and a wall thickness of 10nm and boron nitride nanosheets with a transverse length of 200nm and a thickness of 30nm were selected as raw materials. Equal amounts of boron nitride nanotubes and boron nitride nanosheets were added to dimethylformamide to prepare a slurry with a solid content of 60%. The boron nitride slurry was then subjected to ultrasonic exfoliation for 48 hours. The ultrasonic slurry was then centrifuged at a low speed of 3000r / min for 15 minutes, and then subjected to high-speed centrifugation at a speed of 11000r / min for 30 minutes. The supernatant was then poured to obtain boron nitride nanotubes and boron nitride nanosheets precipitates. The slurry was then freeze-dried at -80°C for 48 hours. The freeze-dried mixed powder of boron nitride nanotubes and boron nitride nanosheets was treated with oxygen plasma for 30 minutes to obtain a hydroxylated boron nitride mixed powder. Then, the hydroxylated boron nitride mixed powder was immersed in 3-ureapropyltrimethoxysilane for 3 hours, and stirred at a speed of 300 r / min and a temperature of 60°C for 45 minutes to amidate the hydroxylated boron nitride. The hydroxylated boron nitride nanosheets s-OH of the boron nitride nanosheets interacted with the silanol obtained by hydrolysis of 3-ureapropyltrimethoxysilane to obtain nanosheets with amide groups at the end. 2. Add 2% polydopamine to the boron nitride slurry to modify the amidated boron nitride, soak it at room temperature for 3 hours, and stir it evenly. Then dissolve 5wt% aramid nanofibers in ethanol at 70℃ and soak it for 2 hours. Add the soaked aramid nanofiber ethanol solution to the amidated boron nitride modified by polydopamine to prepare a boron nitride aramid nanofiber suspension of about 50%, and ultrasonicate it for 2 hours. Divide the prepared boron nitride nanotube / boron nitride nanosheet / aramid nanofiber suspension into 20 portions and electrospin in a staggered manner of 10 vertical and 10 horizontal. Cover the surface of the receiving disc with polytetrafluoroethylene, adjust the speed to 2000r / min, and the spinning time is 3h. The obtained film is subjected to high-temperature hot pressing at 200℃ to obtain a boron nitride self-supporting film. The obtained film has a strength of 20MPa, a thermal conductivity of 40W / mK, and a film density of 60g / m 2 , the porosity is 65%.

[0041] Example 4 Boron nitride nanotubes with a diameter of 50nm, a length of 150μm, and a wall thickness of 10nm and boron nitride nanosheets with a transverse length of 200nm and a thickness of 30nm were selected as raw materials. Equal amounts of boron nitride nanotubes and boron nitride nanosheets were added to dimethylformamide to prepare a slurry with a solid content of 60%. The boron nitride slurry was then subjected to ultrasonic exfoliation for 48 hours. The ultrasonic slurry was then centrifuged at a low speed of 2000r / min for 30 minutes, and then subjected to high-speed centrifugation at a speed of 2000r / min for 20 minutes. The supernatant was then poured to obtain boron nitride nanotubes and boron nitride nanosheets precipitates. The slurry was then freeze-dried at -80°C for 48 hours. The freeze-dried mixed powder of boron nitride nanotubes and boron nitride nanosheets was treated with oxygen plasma for 30 minutes to obtain a hydroxylated boron nitride mixed powder. Then the hydroxylated boron nitride mixed powder was immersed in 3-ureapropyltrimethoxysilane for 3 hours and stirred for 45 minutes at a speed of 300 r / min and a temperature of 50°C to amidate the hydroxylated boron nitride. The hydroxylated boron nitride nanosheets s-OH interacted with the silanol obtained by hydrolysis of 3-ureapropyltrimethoxysilane to obtain nanosheets with amide groups at the end. 2. Add 2% polydopamine to the boron nitride slurry to modify the amidated boron nitride, soak it at room temperature for 1 hour, and stir it evenly. Then dissolve 3wt% aramid nanofibers in ethanol at 70℃ and soak it for 2 hours. Add the soaked aramid nanofiber ethanol solution to the amidated boron nitride modified by polydopamine to prepare a boron nitride aramid nanofiber suspension of about 50%, and ultrasonicate it for 2 hours. Divide the prepared boron nitride nanotube / boron nitride nanosheet / aramid nanofiber suspension into 20 portions and electrospin in a staggered manner of 10 vertical and 10 horizontal. Cover the surface of the receiving disc with polytetrafluoroethylene, adjust the speed to 3000r / min, and the spinning time is 3h. The obtained film is subjected to high-temperature hot pressing at 200℃ to obtain a boron nitride self-supporting film. The obtained film has a strength of 40MPa, a thermal conductivity of 60W / mK, and a film density of 65g / m 2 , the porosity is 50%.

[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a boron nitride self-supporting film by electrospinning, characterized in that: The steps include: S1: preparing mixed powder of boron nitride nanotubes and boron nitride nanosheets; S2: treating the mixed powder of boron nitride nanotubes and boron nitride nanosheets obtained in step S1 with oxygen plasma to obtain hydroxylated boron nitride mixed powder; S3: soaking the hydroxylated boron nitride mixed powder obtained in step S2 in a silane coupling agent, stirring to obtain hydroxylated boron nitride amidation, soaking the hydroxylated boron nitride amidation in polydopamine, stirring to obtain polydopamine-modified amidated boron nitride, wherein the silane coupling agent is 3-ureapropyltrimethoxysilane; S4: the amidated boron nitride modified with polydopamine obtained in step S3 is mixed with the aramid nanofiber ethanol solution, and after ultrasonication, a boron nitride aramid nanofiber suspension is obtained, wherein the mass percentage of the aramid nanofiber in the aramid nanofiber ethanol solution is 3-8wt%; S5: electrospinning the boron nitride aramid nanofiber suspension obtained in step S4 to obtain a film, and subjecting the film to high-temperature hot pressing to obtain a boron nitride self-supporting film.

2. The method for preparing a boron nitride self-supporting film by electrospinning according to claim 1, characterized in that: The preparation of the mixed powder of boron nitride nanotubes and boron nitride nanosheets in step S1 comprises the following steps: dispersing the boron nitride nanotubes and boron nitride nanosheets in an organic solution to prepare a boron nitride slurry, subjecting the boron nitride slurry to ultrasonication and centrifugation to obtain a precipitate, and freeze-drying the precipitate to obtain a mixed powder of boron nitride nanotubes and boron nitride nanosheets; And / or, in step S1, the length of the boron nitride nanotube is 50-150 μm, the diameter of the boron nitride nanotube is 50-150 nm, and the wall thickness of the boron nitride nanotube is 10-30 nm; And / or, in step S1, the lateral length of the boron nitride nanosheet is 50-200 nm, and the thickness of the boron nitride nanosheet is 30-50 nm.

3. The method for preparing a boron nitride self-supporting film by electrospinning according to claim 2, characterized in that: The solid content of the boron nitride slurry in step S1 is 30% to 70%; And / or, the organic solution in step S1 includes one or more of ethanol, dimethyl sulfoxide, dichloromethane, tetrahydrofuran, toluene, and dimethylformamide; And / or, the time for ultrasonication of the boron nitride slurry in step S1 is 24 to 72 hours; And / or, the boron nitride slurry after ultrasonic treatment in step S1 is centrifuged, and the centrifugation includes low-speed centrifugation and high-speed centrifugation, wherein the speed of the low-speed centrifugation is 1000-3000 r / min, the low-speed centrifugation time is 10-25 min, and the speed of the high-speed centrifugation is 8000-20000 r / min, and the high-speed centrifugation time is 15-45 min; And / or, the freeze-drying temperature in step S1 is: -78~-82°C, and the time is 24~48h.

4. The method for preparing a boron nitride self-supporting film by electrospinning according to claim 2, characterized in that: The solid content of the boron nitride slurry in step S1 is 60%; And / or, the organic solution in step S1 is one of tetrahydrofuran or dimethylformamide; And / or, in step S1, the boron nitride slurry is ultrasonicated for 48 hours.

5. The method for preparing a boron nitride self-supporting film by electrospinning according to claim 1, characterized in that: The time of oxygen plasma treatment in step S2 is 20 to 60 minutes.

6. The method for preparing a boron nitride self-supporting film by electrospinning according to claim 1, characterized in that: In step S3, the hydroxylated boron nitride mixed powder is immersed in the silane coupling agent for 1 to 5 hours; And / or, in step S3, the hydroxylated boron nitride mixed powder is immersed in the silane coupling agent and then stirred, wherein the stirring speed is 100 to 500 r / min, the stirring temperature is 40 to 80° C., and the stirring time is 30 to 60 min; And / or, in step S3, the concentration of polydopamine is 1-4%, and the hydroxylated boron nitride is amidated and immersed in polydopamine at room temperature for 1-5 hours.

7. The method for preparing a boron nitride self-supporting film by electrospinning according to claim 1, characterized in that: The method for preparing the aramid nanofiber ethanol solution in step S4 comprises the following steps: dissolving and immersing the aramid nanofiber in ethanol to obtain the aramid nanofiber ethanol solution, wherein the immersion temperature of the aramid nanofiber in ethanol is 50-90° C., and the immersion time is 1.8-2.2 h.

8. The method for preparing a boron nitride self-supporting film by electrospinning according to claim 7, characterized in that: In step S4, the ultrasonic time after the amidated boron nitride modified with polydopamine and the aramid nanofiber ethanol solution are mixed is 1 to 2 hours; The solid content of the boron nitride aramid nanofiber suspension in step S4 is 30-70%.

9. The method for preparing a boron nitride self-supporting film by electrospinning according to claim 1, characterized in that: In step S5, the prepared boron nitride aramid nanofiber suspension is divided into 20 portions, and electrospun in a staggered manner of 10 vertically and 10 horizontally; in step S5, the surface of the receiving disc in the electrospinning is covered with polytetrafluoroethylene, the rotation speed of the receiving disc is 1000-3000 r / min, and the spinning time of the electrospinning is 0.5-3h; And / or, the obtained film is subjected to heat pressing at a temperature of 100 to 300°C.

10. The boron nitride self-supporting film obtained by the method for preparing a boron nitride self-supporting film by electrospinning according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Heat conduction type aramid nano insulation paper and preparation method thereof

    CN108978328A

  • Boron nitride composite high-thermal-conductivity insulating polymer composite material and preparation method thereof

    CN110951254A

  • High-strength heat-conducting modified epoxy resin composite coating material and preparation method thereof

    CN112063301A

  • Method for preparing heat-conducting insulating film based on hexagonal boron nitride

    CN114481355A

  • Filler modification method, modified filler and filled heat-conducting epoxy resin

    CN115819845A